2017
DOI: 10.3390/ijms18020468
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Factor 1 Depletion Sensitizes A172 Glioblastoma Cells to Temozolomide via Suppression of Cancer Stem Cell-Like Properties

Abstract: Heat shock factor 1 (HSF1), a transcription factor activated by various stressors, regulates proliferation and apoptosis by inducing expression of target genes, such as heat shock proteins and Bcl-2 (B-cell lymphoma 2) interacting cell death suppressor (BIS). HSF1 also directly interacts with BIS, although it is still unclear whether this interaction is critical in the regulation of glioblastoma stem cells (GSCs). In this study, we examined whether small interfering RNA-mediated BIS knockdown decreased protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…It follows from the above data that the cancer stemness-related transcriptional activity of HSF1 is regulated via its phosphorylation/dephosphorylation; besides, proteins, such as FBXW7α [166] and BIS [168], can affect the relevant function and expression level of HSF1. Thus, there are several points for modulating HSF1's contribution to the formation/maintenance of the CSC phenotype.…”
Section: Hsf1 and Hsf1-activating Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…It follows from the above data that the cancer stemness-related transcriptional activity of HSF1 is regulated via its phosphorylation/dephosphorylation; besides, proteins, such as FBXW7α [166] and BIS [168], can affect the relevant function and expression level of HSF1. Thus, there are several points for modulating HSF1's contribution to the formation/maintenance of the CSC phenotype.…”
Section: Hsf1 and Hsf1-activating Exposurementioning
confidence: 99%
“…By means of knockdown and overexpression of HSF1 in breast cancer cell lines, a direct contribution of this transcriptional factor to the CSC phenotype was demonstrated: The HSF1 expression level was positively correlated with the CSC phenotype frequency, stemness marker expression, and drug resistance [167]. HSF1 knockdown in sphere-forming human A172 glioblastoma CSCs resulted in failing of the spheroid-forming capacity, reduced expression of SOX2 (a marker of stemness), and downregulation of MMP2 activity; such an addiction of the glioblastoma CSC phenotype to HSF1 was somehow supported the Bcl-2-interacting cell death suppressor (BIS), as BIS depletion led to a decrease in the HSF1 protein level [168]. In a breast cancer model, it was shown how one of the key players in the CSC phenotype formation, β-catenin, is regulated by HSF1 in a phosphorylation-dependent manner: The activating phosphorylation of HSF1 at serine 326 led to HSF1-mediated involvement of the RNA-binding protein HuR (human antigen R), which controls β-catenin mRNA translation [169].…”
Section: Hsf1 and Hsf1-activating Exposurementioning
confidence: 99%
“…TMZ is widely used to treat primary or metastatic brain cancer, which had efficacy on the recovery of patients . It was reported that BIS or HSF1 knockdown combined with TMZ treatment increased tumour apoptosis while cancer stem‐like properties was suppressed, such as SOX2 protein expression . Hao et al demonstrated that resveratrol combination with TMZ had significant efficacy on glioblastoma progression .…”
Section: Introductionmentioning
confidence: 99%
“…cancer stem-like properties was suppressed, such as SOX2 protein expression. 10 Hao et al demonstrated that resveratrol combination with TMZ had significant efficacy on glioblastoma progression. 11 Some studies also explored the effects of TMZ on glioblastoma cells activities.…”
mentioning
confidence: 99%
“…BIS was also shown to co-translocate into the nucleus with HSF1 upon heat shock stress in HeLa cells [ 38 ]. In addition, under glioblastoma stem cell like sphere-forming conditions, BIS depletion is known to decrease HSF1 protein levels and its nuclear localization [ 39 ]. Collectively, these results indicate that BIS might be positively involved in the nuclear translocation of HSF1.…”
Section: Discussionmentioning
confidence: 99%